Earthquake: Impact on Nepalese economy and women - K. Shakya (International Association of Lowland Technology, 2016)
Nepal is one of the 20 most disaster-prone countries in the world. More people are killed by disasters in Nepal than in any other country in South Asia, making Nepal extremely vulnerable to different types of natural disasters like earthquakes, floods, landslides, fire, drought and others. Hence, people faces big or small impact on overall. The aim of the article is to identify the impact of recent earthquake of 25th April and May 12th, 2015 on Nepalese economy and women in Nepal. The article is based on secondary information as published by different sources and further the article updates on economic loss of Nepal due to earthquake and it impact on Nepalese economy and women. It traces the historical background of the earthquake, which occurred in Nepal and follows to identify the impact of recent earthquake on people and properties (damaged by partially and fully). It also presents the loss on various sectors like social, productive, infrastructure and cross cutting sectors, which are indicator of Nepalese economy before and after earthquake. The article also further focuses on the requirement of resources to reconstruct and recover the damaged and lost sectors, concluding that the recent earthquake has greatly impact on Nepalese economy and women.